Political Entrepreneurship di Madura (Studi tentang Kuasa Aktor dalam Demokratisasi Lokal) - Bariroh, Laili; Fakhruddin, M. Anas (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2021)
This article focuses on efforts to find political entrepreneurship for poli-tical actors in Alang-alang Village and the prospects for democracy that are occurring. Based on the research conducted, there are several inte-resting things, including: First, the political entrepreneurship of Alang-alang village Klebun can be seen in the political strategy applied to manage the surrounding actors. Every relationship built by a Klebun to the actors around them is realized as part of the production of power and at the same time maintaining it. Second, in the context of demo-cratization at the local level, political actors in Alang-alang village are trying to get out of the previous centralism of power. The tagline